2018
DOI: 10.3791/56305
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Properties of Aquafaba: Water Recovered from Commercially Canned Chickpeas

Abstract: Chickpea and other pulses are commonly sold as canned products packed in a thick solution or a brine. This solution has recently been shown to produce stable foams and emulsions, and can act as a thickener. Recently interest in this product has been enhanced through the internet where it is proposed that this solution, now called aquafaba by a growing community, can be used a replacement for egg and milk protein. As aquafaba is both new and being developed by an internet based community little is known of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…To our knowledge, scientific peer‐reviewed information regarding aquafaba composition is limited; however, our previous study revealed that aquafaba from commercial chickpea cans consist of 94 g/100 g water, 1.5 g/100 g protein, 0.5 g/100 g ash and the remainder is simple and complex carbohydrates. Fat was not detected (Shim et al ., ). These results are in accordance with previously published data on garbanzo chickpea cooking water (Aquafaba, ; Stantiall et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…To our knowledge, scientific peer‐reviewed information regarding aquafaba composition is limited; however, our previous study revealed that aquafaba from commercial chickpea cans consist of 94 g/100 g water, 1.5 g/100 g protein, 0.5 g/100 g ash and the remainder is simple and complex carbohydrates. Fat was not detected (Shim et al ., ). These results are in accordance with previously published data on garbanzo chickpea cooking water (Aquafaba, ; Stantiall et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Aquafaba from commercial chickpea cans (kabuli cultivars) was recovered as previously described by Shim et al (2018). The chickpea cans were opened, and seed was separated from the aquafaba using a stainless steel mesh kitchen strainer.…”
Section: Aquafaba Preparationmentioning
confidence: 99%
See 3 more Smart Citations